Penerapan Prinsip Etika Bisnis Islam Dalam Peningkatan Entrepreunership Pada Galeri Muslim Mahabatullah Kota Jambi - Dede Kurniadi; Maulana Yusuf; Hareastoma (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this research was to find out the application of the principles of Islamic business ethics in increasing entrepreneurship in Mahabatullah, Jambi City, and to find out the efforts to increase the application of Islamic business ethics principles in Mahabatullah, Jambi City. In this study using qualitative methods. Based on the results of the study, the following conclusions were obtained: 1. The application of the principles of Islamic business ethics in increasing entrepreneurship in Mahabatullah City of Jambi uses indicators of Islamic business ethics in general which are the key to success as a businessman, namely honesty in selling good quality goods, building good relations between colleagues as well as being loose and generous. 2. Efforts to improve the application of the principles of Islamic business ethics in Mahabatullah City of Jambi include improving the ethics of employees towards consumers, selling good quality goods, prohibiting the use of oaths, loose and generous, orderly administration and setting prices transparently.